O'Neill, William (audio interview #1 of 1) - O'Neill, William (4/8/1931 - 10/24/2012); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This single interview with William O'Neill was conducted in the CSULB Oral History Resource Center. The audio quality is good. 1/22/1981